An application of Geometric Process in the Study of HIV Infection - S. Parthasarathy, R. Jaisankar (Recent Research in Science and Technology, 2009)
In the study of HIV infection the expected time to cross the antigenic diversity threshold which means the manifestation of AIDS, the interarrival times between successive sexual contacts play a vital role. The use of the shock models and cumulative damage process is a viable method in this context. Under the assumption that the sequence of interarrival times forms a geometric process the expected time to cross the antigenic diversity threshold and its variance are obtained. Numerical examples using Monte-Carlo simulation study are furnished to substantiate the theoretical results derived in this paper.